Coronary microvascular dysfunction results in impaired coronary flow reserve and altered oxygen balance in a swine model of INOCA with multiple risk factors. (25th November 2020) - Sorop, O; Van De Wouw, J; Van Drie, R.W.A; Joles, J.A; Verhaar, M.C; Merkus, D; Duncker, D.J
Abstract: Introduction: Comorbidities of ischemic heart disease, including diabetes mellitus (DM), hypercholesterolemia and chronic kidney disease (CKD), are associated with coronary microvascular dysfunction (CMD) and may contribute to myocardial "Ischemia and No Obstructive Coronary Artery disease" (INOCA). Purpose: We studied myocardial perfusion and oxygen delivery using a novel swine model with multiple comorbidities. Methods: DM (streptozotocin), HFD (high fat diet) and CKD (renal embolization), were induced in 12 female swine (DM+HFD+CKD), while 12 healthy female swine on a normal diet served as controls (CON). After 6 months, in the absence of coronary atherosclerosis, myocardial perfusion and function were studied at rest and during treadmill exercise. Results DM+HFD+CKD animals showed hyperglycemia, hypercholesterolemia and impaired kidney function. During exercise, DM+HFD+CKD demonstrated impaired myocardial blood flow and oxygen delivery, necessitating higher myocardial oxygen extraction (despite reduced capillary density), resulting in lower coronary venous oxygen levels, (Fig. 1). These perturbations were associated with lower myocardial efficiency, requiring higher oxygen consumption for a given level of myocardial work (Fig. 1), lower myocardial lactate consumption, stroke volume and LVdP/dtmax, suggestive of myocardial ischemia and dysfunction. Furthermore DM+HFD+CKD showed a reduction in adenosine-recruitable coronary flow reserve (2.69±0.26 vs 3.64±0.2 in CON, p<0.05), which was exclusively the result of an increase in basal coronary blood flow, while maximal coronary flow per gram of myocardium was maintained. The latter was consistent with the unchanged arteriolar wall/lumen ratio, arteriolar density and peri-arteriolar collagen content. eNOS blockade indicated loss of NO bioavailability in DM+HFD+CKD swine in vivo (Fig. 1), which was supported by blunted endothelium-dependent vasodilation to bradykinin in isolated small arteries. These findings suggest that changes in coronary microvascular function rather than structure contributed to the perturbations in myocardial oxygen delivery. Conclusion: Common comorbidities result in CMD and impaired NO bioavailability rather than structural alterations in the microvasculature in swine, in the absence of appreciable atherosclerosis. These alterations are severe enough to produce perturbations in myocardial oxygen balance and coronary metabolism and function, particularly during exercise, resembling key features of INOCA. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): This study was supported by grants from the European Commission FP7-Health-2010 grant MEDIA-261409, the Netherlands CardioVascular Research Initiative: an initiative with support of the Dutch Heart Foundation [CVON2014-11 (RECONNECT)].